Retromedia-in-practice: A practice theory approach for rethinking old and new media technologies. (August 2019) - Magaudda, Paolo; Minniti, Sergio
The article aims at investigating the persistence and comeback of old media technologies (phenomena we define, in short, 'retromedia') by developing a distinctive theoretical approach named retromedia-in-practice and based on practice theory. Far from being abandoned and forgotten, many old media devices and artefacts (such as vinyl records, cassette tapes, analogue photographic cameras, early videogames and brick mobile phones, to mention just a few notable examples) are nowadays readopted by young generations and niche media subcultures. However, most of the existing literature focusing on these cases has limits and shortfalls, resulting in a partial and misleading understanding of these phenomena: scholars and theorists often put at the centre the cultural fascination for vintage objects and the nostalgia effect; other studies rely on a taken-for-granted distinction between old and new media; the relational and processual nature of media change is rarely addressed; and in general, research lacks a framework capable of adequately integrating symbolic processes with material and technological features. In order to cope with these shortfalls, the article adopts the approach of practice theory, which enables to focus not on the media themselves, but on the practices associated with them. After presenting the distinctive framework of analysis, we exemplify our approach by analysing three different cases coming from music (vinyl records), photography (Polaroid-like instant photography) and videogaming (the 'consolization' of old arcade games). These case studies rely on original empirical data coming from authors' qualitative research. The article concludes by arguing that a shift from considering retromedia as objects or discourses to retromedia-in-practice allows to both address the processual nature of retromedia and propose an interpretation that keeps together media materiality, their meanings and also the embodied activities and behaviours that are attached to them.